Capturing complex human behaviors in representative sports contexts with a single camera - Duarte, Ricardo (2019)
Background and objective. In the last years, several motion analysis methods have been developed without considering representative contexts for sports performance. The purpose of this paper was to explain and underscore a straightforward method to measure human behavior in these contexts. Material and methods. Procedures combining manual video tracking (with TACTO device) and bidimensional reconstruction (through direct linear transformation) using a single camera were used in order to capture kinematic data required to compute collective variable(s) and control parameter(s). These procedures were applied to a 1vs1 association football task as an illustrative subphase of team sports and will be presented in a tutorial fashion. Results. Preliminary analysis of distance and velocity data identified a collective variable (difference between the distance of the attacker and the defender to a target defensive area) and two nested control parameters (interpersonal distance and relative velocity). Conclusions. Findings demonstrated that the complementary use of TACTO software and direct linear transformation permit to capture and reconstruct complex human actions in their context in a low dimensional space (information reduction).